Optical Glass and Optical Elements

Optical glass compositions with controlled component ratios provide a high refractive index and low thermal expansion, addressing precision pressing challenges and enhancing thermal stability for optical elements.

JP7612003B2Active Publication Date: 2025-01-10CDGM OPTICAL GLASS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023515188
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-07
Filing Date
2021-07-21
Publication Date
2025-01-10
Estimated Expiration
2041-07-21

AI Technical Summary

Technical Problem

Existing optical glasses face challenges in achieving a high refractive index with a low coefficient of thermal expansion, which can lead to rupture during thermal processing and deteriorate thermal shock resistance, making them unsuitable for precision pressing.

Method used

Optical glass compositions containing specific ratios of components such as B2O3, La2O3, Gd2O3, ZrO2, ZnO, WO3, TiO2, and optional additives like SiO2, Y2O3, Yb2O3, Nb2O5, RO, Al2O3, and clarifying agents, with controlled ratios to achieve a refractive index of 1.85-1.91 and thermal expansion coefficient of 100×10^-7/K or less, suitable for precision pressing.

Benefits of technology

The glass exhibits a low transition temperature and thermal expansion coefficient, enabling effective precision press molding with improved thermal stability and optical properties, suitable for various optical elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612003000001
    Figure 0007612003000001
  • Figure 0007612003000002
    Figure 0007612003000002
Patent Text Reader

Abstract

The present invention provides an optical glass containing the following components by weight: B2O3: 8-20%, La2O3: 21-40%, Gd2O3: 6-20%, ZrO2: 1-10%, ZnO: 7-20%, WO3: 8-20%, TiO2: greater than 0 and less than 10%, with (WO3 + ZnO) / (La2O3 + TiO2 + ZrO2) being 0.3-1.5. Thanks to the rational component design, the optical glass obtained by the present invention has a low transition temperature and thermal expansion coefficient, making it suitable for precision pressing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to optical glass, and more particularly to optical glass that has a low thermal expansion coefficient and a high refractive index suitable for precision pressing, and to a glass preform and an optical element made therefrom. [Background technology]

[0002] Optical glass is a glass material used to manufacture lenses, prisms, mirrors, windows, etc. in optical instruments and mechanical systems. At present, the main method of manufacturing optical glass as optical elements is precision press molding (including direct pressing and secondary pressing). Lenses manufactured using precision pressing technology do not need to be ground and polished, which can reduce raw material consumption, reduce human and material costs, and reduce environmental pollution. Therefore, this technology can be used to mass-produce optical elements at low cost. Precision pressing is to press mold a glass preform with a high-precision mold having a predetermined product shape at a certain temperature and pressure to obtain a glass product with the shape and optical function of the finished product. Precision pressing technology can be used to manufacture a variety of optical glass products, such as spherical lenses, aspherical lenses, prisms, and diffraction gratings.

[0003] When performing precision press molding, it is necessary to press mold a glass preform at high temperatures (usually above the glass transition temperature of 20 to 60°C) in order to transfer the highly precise mold surface to the glass product. In this case, the molding mold is subjected to high temperature and pressure shocks, and even if there is a protective gas, the surface of the mold is easily oxidized or eroded. In order to extend the life of the mold and suppress damage to the mold due to the high temperature environment, it is necessary to lower the press temperature. Therefore, the transition temperature (T g ) should be as low as possible.

[0004] With the progress of science and technology, the renewal of optoelectronic information products is continuing, the demand for optical glass is getting bigger and bigger, and the performance requirements for optical glass are becoming more stringent. For example, if the thermal expansion coefficient of optical glass is too large, it is easy to burst during the thermal processing process, which reduces the yield rate of glass elements and also deteriorates the thermal shock resistance of optical glass. For the same radius of curvature, the higher the refractive index of a glass, the larger the imaging field that can be obtained. As optical devices become increasingly smaller, the demand for high refractive index glass tends to increase. Summary of the Invention [Problem to be solved by the invention]

[0005] The technical problem to be solved by the present invention is to provide a high refractive index optical glass that has a low thermal expansion coefficient and is suitable for precision pressing. [Means for solving the problem]

[0006] The technical solutions adopted in the present invention to solve the technical problems are as follows: (1) Optical glass containing the following components by weight: B2O3: 8-20%, La2O3: 21-40%, Gd2O3: 6-20%, ZrO2: 1-10%, ZnO: 7-20%, WO3: 8-20%, TiO2: over 0 and up to 10%, (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.3-1.5. (2) The optical glass according to (1), further comprising the following components by weight: SiO2: 0-9%, and / or Y2O3: 0-10%, and / or Yb2O3: 0-10%, and / or Nb2O5: 0-8%, and / or Rn2O: 0-10%, and / or RO: 0-10%, and / or Al2O3: 0-5%, and / or Ta2O5: 0-5%, and / or a fining agent: 0-1%, wherein the Rn2O is one or more of Li2O, Na2O, and K2O, the RO is one or more of MgO, CaO, SrO, and BaO, and the fining agent is one or more of Sb2O3, SnO2, SnO, and CeO2. (3) An optical glass containing, as necessary components, B2O3, La2O3, Gd2O3, ZrO2, ZnO, WO3, and TiO2, the components being expressed in weight percent: (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.3 to 1.5, and the refractive index n of said optical glass is d is 1.85~1.91, Abbe number ν d is 32~38.5, thermal expansion coefficient α 100 / 300℃ is 100 x 10 -7 / K or less. (4) The optical glass according to (3), comprising the following components by weight: B2O3: 8-20%, and / or La2O3: 21-40%, and / or Gd2O3: 6-20%, and / or ZrO2: 1-10%, and / or ZnO: 7-20%, and / or WO3: 8-20%, and / or TiO2: more than 0 and 10% or less, and / or SiO2: 0-9%, and / or Y2O3: 0-10%, and / or Yb2O3: 0-10%, and / or Nb2O5: 0-8%, and and / or Rn2O: 0-10%, and / or RO: 0-10%, and / or Al2O3: 0-5%, and / or Ta2O5: 0-5%, and / or fining agent: 0-1%, wherein the Rn2O is one or more of Li2O, Na2O, and K2O, the RO is one or more of MgO, CaO, SrO, and BaO, and the fining agent is one or more of Sb2O3, SnO2, SnO, and CeO2. (5) Optical glass consisting of the following components by weight: B2O3: 8-20%, La2O3: 21-40%, Gd2O3: 6-20%, ZrO2: 1-10%, ZnO: 7-20%, WO3: 8-20%, TiO2: 0-10%, SiO2: 0-9%, Y2O3: 0-10%, Yb2O3: 0-10%, Nb2O5: 0-8%, Rn2O: 0-10%, RO: 0-10%, Al2O3: 0-5%, Ta2 O5: 0-5%, fining agent: 0-1%, (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.3-1.5, the Rn2O is one or more of Li2O, Na2O, K2O, RO is one or more of MgO, CaO, SrO, BaO, and the fining agent is one or more of Sb2O3, SnO2, SnO, CeO2. (6) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following nine conditions: 1) Nb2O5 / Y2O3 is 0.1~2.5; 2) Y2O3 / WO3 is 0.05~1.0; 3) Y2O3 / TiO2 is 0.2~3.5; 4) 5×Nb2O5 / (WO3+Gd2O3) is 0.05~1.5; 5) ZnO / La2O3 is 0.2~0.8; 6) Gd2O3 / (La2O3+Y2O3) is 0.2~0.8; 7) (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.5~1.0; 8) 5×Li2O / (TiO2+SiO2) is 0.05~5.0; 9) Nb2O5 / WO3 is 0.03~0.7. (7) An optical glass according to any one of (1) to (5), comprising the following components by weight: B2O3: 10-18%, and / or La2O3: 25-38%, and / or Gd2O3: 8-18%, and / or ZrO2: 1-8%, and / or ZnO: 8-18%, and / or WO3: 10-18%, and / or TiO2: 0.5-7%, and / or SiO2: 0.5-9%, and / or Y2O3: more than 0 and not more than 6%, and / or Yb2O3: 0-5%, and / or Nb2O5: 0.5-6%, and / or Rn2O: 0-5%, and / or RO: 0-5%, and / or Al2O3: 0-2%, and / or Ta2O5: 0-2%, and / or fining agent: 0-0.5%, wherein the Rn2O is one or more of Li2O, Na2O, and K2O, the RO is one or more of MgO, CaO, SrO, and BaO, and the fining agent is one or more of Sb2O3, SnO2, SnO, and CeO2. (8) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following nine conditions: 1) Nb2O5 / Y2O3 is 0.25~1.5; 2) Y2O3 / WO3 is 0.1-0.6; 3) Y2O3 / TiO2 is 0.5~2.0; 4) 5×Nb2O5 / (WO3+Gd2O3) is 0.1~1.0; 5) ZnO / La2O3 is 0.3~0.7; 6) Gd2O3 / (La2O3+Y2O3) is 0.25~0.65; 7) (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.6~0.9; 8) 5×Li2O / (TiO2+SiO2) is 0.1~2.0; 9) Nb2O5 / WO3 is 0.05~0.5. (9) An optical glass according to any one of (1) to (5), comprising the following components by weight: B2O3: 11 to 17%, and / or La2O3: 28 to 35%, and / or Gd2O3: 9.5 to 16%, preferably Gd2O3: 11 to 16%, and / or ZrO2: 2 to 6%, and / or ZnO: 10 to 16%, preferably ZnO: 11 to 16%, and / or WO3: 12 to 17%, and / or TiO2: 1 to 5%, and / or SiO2: 1 to 8%, preferably SiO2: 2 to 6%, and / or Y2O3: 1 to 5%, and / or Yb2O3: 0.5 to 0.5%. and / or Nb2O5: 1-5%, and / or Rn2O: 0.5-3%, and / or RO: 0-2%, and / or Al2O3: 0-1%, and / or Ta2O5: 0-1%, and / or fining agent: 0-0.1%, wherein the Rn2O is one or more of Li2O, Na2O, and K2O, the RO is one or more of MgO, CaO, SrO, and BaO, and the fining agent is one or more of Sb2O3, SnO2, SnO, and CeO2. (10) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following nine conditions: 1) Nb2O5 / Y2O3 is 0.3~0.8; 2) Y2O3 / WO3 is 0.1-0.4; 3) Y2O3 / TiO2 is 0.8~1.3; 4) 5×Nb2O5 / (WO3+Gd2O3) is 0.15~0.5; 5) ZnO / La2O3 is 0.35~0.65; 6) Gd2O3 / (La2O3+Y2O3) is 0.35~0.55; 7) (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.7~0.85; 8) 5×Li2O / (TiO2+SiO2) is 0.2~1.0; 9) Nb2O5 / WO3 is 0.06~0.4. (11) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following five conditions: 1) Nb2O5 / Y2O3 is 0.4~0.7; 2) 5×Nb2O5 / (WO3+Gd2O3) is 0.2~0.4; 3) ZnO / La2O3 is 0.4~0.55; 4) 5×Li2O / (TiO2+SiO2) is 0.3~0.8; 5) Nb2O5 / WO3 is 0.08~0.3. (12) An optical glass according to any one of (1) to (5) containing the following components by weight: Li2O: 0 to 6%, preferably more than 0 and not more than 4% Li2O, more preferably 0.1 to 3%, still more preferably 0.5 to 2% Li2O, and / or Na2O: 0 to 5%, preferably 0 to 3% Na2O, more preferably 0 to 2% Na2O, and / or K2O: 0 to 5%, preferably 0 to 3% K2O, more preferably 0 to 2% K2O. (13) The optical glass according to any one of (1) to (5), which does not contain Ta2O5, and / or does not contain GeO2, and / or does not contain F, and / or does not contain Al2O3, and / or does not contain RO, and / or does not contain P2O5, and / or does not contain Bi2O3 as its components. (14) The optical glass according to any one of (1) to (5), wherein the refractive index n d is 1.85 to 1.91, preferably 1.86 to 1.90, more preferably 1.88 to 1.90, and the Abbe number ν d is 32 to 38.5, preferably 33 to 37.5, and more preferably 34 to 37. (15) An optical glass according to any one of (1) to (5), wherein the acid resistance stability D of the optical glass is Ais Class 3 or more, preferably Class 2 or more, more preferably Class 1, and / or water resistance D W is class 2 or more, preferably class 1, and / or density ρ is 5.50 g / cm 3 Less than 5.40 g / cm 3 Less than or equal to 5.30 g / cm 3 or less, more preferably 5.20 g / cm 3 Below, and / or λ 70 is 410 nm or less, preferably λ 70 is 405 nm or less, more preferably λ 70 is 400 nm or less, and more preferably λ 70 is 395 nm or less, and / or λ5 is 375 nm or less, preferably λ5 is 370 nm or less, more preferably λ5 is 365 nm or less, even more preferably λ5 is 360 nm or less. (16) The optical glass according to any one of (1) to (5), wherein the thermal expansion coefficient α of the optical glass is 100 / 300℃ is 100 x 10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 90×10 -7 / K or less, and / or the transition temperature T g is 620° C. or less, preferably 610° C. or less, more preferably 600° C. or less, and / or crystal The upper limit temperature is 1250°C or lower, preferably 1200°C or lower, more preferably 1180°C or lower, and further preferably 1160°C or lower. (17) A glass preform produced from the optical glass according to any one of (1) to (16). (18) An optical element produced from the optical glass according to any one of (1) to (16) or the glass preform according to (17). (19) An optical instrument comprising the optical glass according to any one of (1) to (16) and / or the optical element according to (18). Effect of the Invention

[0007] The beneficial effects of the present invention are as follows: Due to the rational component design, the optical glass obtained by the present invention has a relatively low transition temperature and thermal expansion coefficient, and is suitable for precision press molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the embodiments of the optical glass according to the present invention will be described in detail, but the present invention is not limited to the embodiments described below, and can be practiced with appropriate modifications within the scope of the object of the present invention. Furthermore, although some omissions are made, the gist of the present invention is not limited by the repetition of the description, and hereinafter, the optical glass of the present invention may be simply referred to as glass.

[0009] [Optical glass] The range of the components of the optical glass of the present invention will be described below. In this description, the content and total content of each component will be expressed in weight percent (wt%) unless otherwise specified. In other words, the content and total content of each component will be expressed in weight percent relative to the total weight of the glass material converted into an oxide composition. "Converted into an oxide composition" here refers to the case where the total weight of the oxide material when the oxide, complex salt, hydroxide, etc. used as the raw material of the optical glass composition of the present invention is decomposed and converted into an oxide during melting is taken as 100%. Specifically, the numerical ranges described herein include upper and lower limits, and the terms "greater than or equal to" and "less than or equal to" include the endpoints, and all integers and fractions subsumed within the range, but are not limited to the specific values ​​set forth when the range is limited. As used herein, "and / or" is inclusive, e.g., "A and / or B" means A only, B only, or both A and B.

[0010] <Required and optional ingredients> In the present invention, B2O3 is a network forming component, which improves the thermal stability of glass, improves the meltability of glass, and furthermore, can obtain glass without molten glass raw material residue. In the present invention, 8% or more of B2O3 is added to obtain the above-mentioned effects, and the content of B2O3 is preferably 10% or more, and more preferably 11% or more. However, if the content of B2O3 is too high, the refractive index of the glass decreases and the chemical stability deteriorates, so in the present invention, the upper limit of the content of B2O3 is 20%, preferably 18%, and more preferably 17%.

[0011] SiO2 plays a role in improving the chemical stability of glass, maintaining a viscosity suitable for forming molten glass, and reducing erosion of refractories, but if the content is too high, it becomes difficult to melt glass and is disadvantageous in lowering the glass transition temperature. Therefore, in the present invention, the content of SiO2 is 9% or less, preferably 0.5 to 9%, more preferably 1 to 8%, and further preferably 2 to 6%.

[0012] La2O3 is a component with a high refractive index and low light dispersion, and can be added to glass to increase the refractive index of glass, adjust the light dispersion, and reduce the high-temperature viscosity of glass. In the present invention, the content of La2O3 is 21% or more, preferably the content of La2O3 is 25% or more, and more preferably the content of La2O3 is 28% or more. On the other hand, by limiting the content of La2O3 to 40% or less, the stability of glass can be improved, the devitrification of glass can be reduced, and the increase in the refractive index temperature coefficient and Abbe number can be suppressed from exceeding the design requirements. Therefore, the content of La2O3 is 40% or less, preferably 38% or less, and more preferably 35% or less.

[0013] In the present invention, the addition of 6% or more of Gd2O3 improves the chemical stability of the optical glass and adjusts the thermal expansion coefficient and refractive index of the glass. Therefore, the Gd2O3 content is preferably 8% or more, more preferably 9.5% or more, and even more preferably 11% or more. However, if the Gd2O3 content exceeds 20%, the devitrification resistance of the glass deteriorates and the glass transition temperature increases. Therefore, in the present invention, the Gd2O3 content is 20% or less, preferably 18% or less, and more preferably 16% or less.

[0014] In the present invention, it is preferable to further include 10% or less of Y2O3. By adding Y2O3 and La2O3 simultaneously, the melting property and devitrification resistance of the glass are improved while maintaining a high refractive index and low dispersion. However, if the content of Y2O3 exceeds 10%, the stability and devitrification resistance of the glass decrease, and the transition temperature increases. Therefore, the content of Y2O3 is 0 to 10%, and preferably more than 0 and 6% or less. In some embodiments, by adding 1% or more of Y2O3, the melting property and devitrification resistance of the glass decrease, and the transition temperature increases. crystal The upper limit temperature and density can also be reduced. Therefore, in the present invention, the content of Y2O3 is more preferably 1 to 5%.

[0015] In some embodiments, when Gd2O3 / (La2O3+Y2O3) is less than 0.2, the stability of the glass is reduced, the temperature coefficient of refractive index is increased, and the glass is affected by temperature changes during use and becomes larger; when Gd2O3 / (La2O3+Y2O3) is more than 0.8, the wear resistance of the glass is deteriorated and the density is increased. Therefore, it is preferable that Gd2O3 / (La2O3+Y2O3) is 0.2-0.8, more preferably Gd2O3 / (La2O3+Y2O3) is 0.25-0.65, and even more preferably Gd2O3 / (La2O3+Y2O3) is 0.35-0.55.

[0016] Yb2O3 is also a component that imparts a high refractive index and low dispersion to the glass, and is an optional component in the present invention. If its content exceeds 10%, anti-crystallineand chemical stability decreases. Therefore, the content of Yb2O3 is limited to 0 to 10%, preferably 0 to 5%, more preferably 0 to 2%, and further preferably no Yb2O3 is contained.

[0017] In the glass of the present invention, ZnO adjusts the refractive index and dispersion of the glass, lowers the transition temperature, and anti-crystalline and improves the stability of the glass, and at the same time, ZnO reduces the high-temperature viscosity of the glass, allowing the glass to be melted at a relatively low temperature, and can increase the transmittance of the glass. In the present invention, 7% or more of ZnO is added to obtain the above effects, and the ZnO content is preferably 8% or more, more preferably 10% or more, and even more preferably 11% or more. On the other hand, if the ZnO content exceeds 20%, the abrasion resistance of the glass deteriorates, making it difficult to mold, and the glass becomes unstable. anti-crystalline Therefore, the ZnO content is limited to 20% or less, preferably 18% or less, and more preferably 16% or less.

[0018] In some embodiments of the present invention, the ratio of the ZnO content to the La2O3 content, ZnO / La2O3, is set to 0.2 or more to improve the chemical stability and the refractive index temperature coefficient of the glass. However, if the ZnO / La2O3 ratio exceeds 0.8, the glass anti-crystalline Therefore, the content of ZnO / La2O3 is preferably 0.2 to 0.8, more preferably ZnO / La2O3 is 0.3 to 0.7, even more preferably ZnO / La2O3 is 0.35 to 0.65, and still more preferably ZnO / La2O3 is 0.4 to 0.55.

[0019] WO3 can increase the refractive index and mechanical strength of glass and lower the glass transition temperature. In the present invention, 8% or more of WO3 is added to obtain the above effects, and the lower limit of the WO3 content is preferably 10%, more preferably 12%. If the WO3 content exceeds 20%, the thermal stability of the glass decreases and the devitrification resistance decreases. Therefore, the upper limit of the WO3 content is 20%, preferably 18%, more preferably 17%.

[0020] In some embodiments of the present invention, if Y2O3 / WO3 is less than 0.05, the density of the glass increases, which is disadvantageous for reducing the weight of the glass, and if Y2O3 / WO3 exceeds 1.0, the thermal stability of the glass decreases. Therefore, Y2O3 / WO3 is preferably 0.05 to 1.0, more preferably 0.1 to 0.6, and even more preferably 0.1 to 0.4.

[0021] Nb2O5 is a component with a high refractive index and high light dispersion, which can increase the refractive index and devitrification resistance of glass and reduce the thermal expansion coefficient of glass. If the content of Nb2O5 is too high, the thermal stability and chemical stability of glass are reduced, and the light transmittance is reduced. Therefore, in the present invention, the content of Nb2O5 is 0 to 8%, preferably 0.5 to 6%, and more preferably 1 to 5%.

[0022] The inventors have found through a large amount of experimental research that in some embodiments of the present invention, Nb2O5, WO3 and Gd2O3 generate a complex synergistic effect in the glass, and in particular, by controlling 5×Nb2O5 / (WO3+Gd2O3) within the range of 0.05-1.5, the glass can obtain good heat press stability and at the same time have a suitable degree of wear. Preferably, 5×Nb2O5 / (WO3+Gd2O3) is 0.1-1.0. Furthermore, by controlling 5×Nb2O5 / (WO3+Gd2O3) within the range of 0.15-0.5, the thermal expansion coefficient of the glass can be further optimized. Therefore, more preferably, 5×Nb2O5 / (WO3+Gd2O3) is 0.15-0.5, and even more preferably, 5×Nb2O5 / (WO3+Gd2O3) is 0.2-0.4.

[0023] In some embodiments of the present invention, the Nb2O5 / Y2O3 ratio is 0.1 or more, so that the glass anti-crystalline However, if Nb2O5 / Y2O3 exceeds 2.5, the glass tends to become colored and the light transmittance decreases. Therefore, Nb2O5 / Y2O3 is preferably 0.1 to 2.5, more preferably 0.25 to 1.5, even more preferably 0.3 to 0.8, and even more preferably 0.4 to 0.7.

[0024] In some embodiments of the present invention, controlling Nb2O5 / WO3 within the range of 0.03 to 0.7 helps improve the thermal stability of the glass and optimize the chemical stability of the glass, preferably Nb2O5 / WO3 is 0.05 to 0.5, more preferably Nb2O5 / WO3 is 0.06 to 0.4, and even more preferably Nb2O5 / WO3 is 0.08 to 0.3.

[0025] TiO2 can increase the refractive index and dispersion of glass, and adding an appropriate amount of TiO2 can make glass more stable and reduce the viscosity of glass. However, when the TiO2 content exceeds 10%, the glass crystalThe glass transition temperature increases, and the glass becomes more likely to be colored during press molding. Therefore, in the present invention, the TiO2 content is more than 0 and 10% or less, preferably the TiO2 content is 0.5 to 7%, and more preferably 1 to 5%.

[0026] In some embodiments of the present invention, the weather resistance of glass can be improved by controlling the ratio Y2O3 / TiO2 of the Y2O3 content to the TiO2 content to 0.2 or more, but if Y2O3 / TiO2 exceeds 3.5, the degree of bubbles in the glass deteriorates and the hardness decreases. Therefore, Y2O3 / TiO2 is preferably 0.2 to 3.5, more preferably 0.5 to 2.0, and even more preferably 0.8 to 1.3.

[0027] ZrO2 is a component with a high refractive index and low light dispersion. By adding it to glass, it increases the refractive index of the glass, adjusts the dispersion, and improves the glass's anti-crystalline In the present invention, the above effect is obtained by adding ZrO2 at 1% or more, and preferably the content of ZrO2 is 2% or more. If the content of ZrO2 exceeds 10%, it becomes difficult to melt the glass, the melting temperature increases, and furthermore, inclusions are generated inside the glass, which may reduce the transmittance. Therefore, the content of ZrO2 is 10% or less, preferably 8% or less, and more preferably 6% or less.

[0028] In some embodiments of the present invention, the ratio (WO3+ZnO) / (La2O3+TiO2+ZrO2) of the total content of WO3 and ZnO (WO3+ZnO) to the total content of La2O3, TiO2, and ZrO2 (La2O3+TiO2+ZrO2) is controlled within the range of 0.3 to 1.5, so that the glass can have a lower transition temperature and a lower thermal expansion coefficient. Therefore, in the present invention, the ratio (WO3+ZnO) / (La2O3+TiO2+ZrO2) is preferably 0.3 to 1.5, and more preferably 0.5 to 1.0. Furthermore, by controlling (WO3+ZnO) / (La2O3+TiO2+ZrO2) within the range of 0.6 to 0.9, the degree of bubbles and the degree of abrasion of the glass can be optimized. Therefore, it is more preferable that (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.6 to 0.9, and even more preferable that (WO3+ZnO) / (La2O3+TiO2+ZrO2) is 0.7 to 0.85.

[0029] Rn2O is an alkali metal oxide, and Rn2O is one or more of Li2O, Na2O, and K2O, which can improve the melting property of glass and lower the glass transition temperature, but if the content of Rn2O exceeds 10%, the devitrification resistance of the glass deteriorates and the refractive index decreases significantly. Therefore, in the present invention, the content of Rn2O is 0 to 10%, preferably 0 to 5%, and more preferably 0.5 to 3%.

[0030] Although Li2O can lower the glass transition temperature, a high Li2O content is detrimental to the acid resistance stability and thermal expansion coefficient of the glass. Therefore, in the present invention, the Li2O content is 6% or less, preferably more than 0 and 4% or less, more preferably 0.1 to 3%, and further preferably 0.5 to 2%.

[0031] In some embodiments of the present invention, the viscosity of the glass can be optimized and the degree of stripes and bubbles can be improved by controlling the value of 5×Li2O / (TiO2+SiO2) within the range of 0.05 to 5.0. Therefore, it is preferable that 5×Li2O / (TiO2+SiO2) is 0.1 to 2.0. Furthermore, it is possible to clearly improve the press workability of the glass and reduce the probability of clouding of the glass during press work by controlling the value of 5×Li2O / (TiO2+SiO2) within the range of 0.2 to 1.0. Therefore, it is more preferable that 5×Li2O / (TiO2+SiO2) is 0.2 to 1.0, and even more preferable that 5×Li2O / (TiO2+SiO2) is 0.3 to 0.8.

[0032] Na2O can improve the melting property of glass, enhance the melting effect of glass, and lower the transition temperature of glass, but if the content of Na2O exceeds 5%, the chemical stability and weather resistance of glass will decrease. Therefore, the content of Na2O is 0-5%, preferably the content of Na2O is 0-3%, and more preferably the content of Na2O is 0-2%.

[0033] Although K2O can improve the thermal stability and meltability of glass, if its content exceeds 5%, the devitrification resistance of the glass decreases and the chemical stability of the glass deteriorates. Therefore, in the present invention, the K2O content is 5% or less, preferably the K2O content is 0 to 3%, and more preferably the K2O content is 0 to 2%.

[0034] RO is an alkaline earth metal oxide, and RO is one or more of MgO, CaO, SrO, and BaO. Adding RO to glass can improve the meltability of glass and lower the glass transition temperature, but if the RO content exceeds 10%, the devitrification resistance of glass decreases. Therefore, in the present invention, the RO content is 0 to 10%, preferably 0 to 5%, more preferably 0 to 2%, and further preferably does not contain RO.

[0035] Although Al2O3 can improve the chemical stability of glass, if its content exceeds 5%, the melting property and transmittance of glass deteriorate. Therefore, in the present invention, the content of Al2O3 is 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and further preferably no Al2O3 is contained.

[0036] Ta2O5 can increase the refractive index and improve the devitrification resistance of the glass, but if its content is too high, the chemical stability of the glass decreases, making it difficult to control the optical constants within the desired range. On the other hand, Ta2O5 is very expensive compared to other components, and from the practical and cost perspectives, its amount should be reduced as much as possible. Therefore, in the present invention, the content of Ta2O5 is limited to 0-5%, preferably 0-2%, more preferably 0-1%, and further preferably does not contain Ta2O5.

[0037] In the present invention, the clarification effect of glass can be improved by adding one or more of Sb2O3, SnO, SnO2, and CeO2 components in an amount of 0 to 1% as a clarifier, and the content of the clarifier is preferably 0 to 0.5%, more preferably 0 to 0.1%. If the content of Sb2O3 exceeds 1%, the clarification effect of glass tends to decrease, and at the same time, due to its strong oxidizing action, the corrosion of the platinum or platinum alloy container used for melting the glass and the deterioration of the molding die are accelerated. Therefore, in the present invention, the amount of Sb2O3 added is preferably 0 to 1%, more preferably 0 to 0.5%, and even more preferably 0 to 0.1%. SnO and SnO2 may be added as clarifiers, but if the content exceeds 1%, the glass tends to be colored more easily, and when the glass is heated and softened to be remolded by press molding or the like, Sn becomes the starting point of nucleation, and devitrification tends to occur. Therefore, in the present invention, the content of SnO2 is preferably 0 to 1%, more preferably 0 to 0.5%, even more preferably 0 to 0.1%, and even more preferably none. The content of SnO is preferably 0 to 1%, more preferably 0 to 0.5%, even more preferably 0 to 0.1%, and even more preferably none. The function and the ratio of the amount of CeO2 added are the same as those of SnO2, and the content is preferably 0 to 1%, more preferably 0 to 0.5%, even more preferably 0 to 0.1%, and even more preferably none.

[0038] An appropriate amount of F (fluorine) can be added to the glass of the present invention. However, in some embodiments, the addition of F reduces the stability of the glass and decreases the resistance to devitrification, and its volatility causes instability of the optical constants of the glass and worsens stripes, so it is preferable not to include F.

[0039] Although a suitable amount of GeO2 can be added to the glass of the present invention, in some embodiments, the addition of GeO2 reduces the transmittance of the glass, and since GeO2 is an expensive raw material and reduces the economic efficiency of the glass, it is preferable not to include GeO2.

[0040] Although a suitable amount of P2O5 can be added to the glasses of the invention, in some embodiments it is preferred that the glass does not contain P2O5, since the addition of P2O5 to the glass makes it difficult to obtain the desired high refractive index and reduces the resistance of the glass to devitrification.

[0041] The glasses of the invention can contain a suitable amount of Bi2O3, but in some embodiments it is preferred not to include Bi2O3 since the addition of Bi2O3 reduces the light transmittance of the glass, impairs its abrasion resistance and chemical stability, and significantly increases its density.

[0042] <Ingredients that should not be included> In the glass of the present invention, even when oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained alone or in combination in small amounts, the glass is colored and specific wavelengths in the visible light region are absorbed, weakening the visible light transmission effect of the present invention. Therefore, it is preferable that optical glasses which require wavelength transmittance in the visible light region in particular not actually contain such oxides.

[0043] In recent years, there has been a trend to restrict the use of oxides of Th, Cd, Tl, Os, Be and Se as harmful chemicals, and environmental protection efforts are required not only in the glass manufacturing process, but also in the processing process and disposal of the finished product. Therefore, when the impact on the environment is important, it is preferable that they are not included except for unavoidable contamination. This makes the optical glass actually free of substances that pollute the environment. Therefore, the optical glass of the present invention can be manufactured, processed and disposed of without taking special environmental measures.

[0044] In consideration of the environment, the optical glass of the present invention preferably does not contain As2O3 and PbO. As2O3 has the effect of removing bubbles and preventing coloration of the glass, but the addition of As2O3 increases platinum erosion in the glass melting furnace, especially the platinum melting furnace, so that more platinum ions enter the glass, adversely affecting the service life of the platinum melting furnace.

[0045] The terms "not added," "not included," and "0%" used herein mean that the component was not intentionally added as a raw material for the glass of the present invention. However, impurities or components that are not intentionally added as raw materials and / or equipment for producing the glass may be present in small or trace amounts in the final glass, and are also covered by the present invention.

[0046] The characteristics of the optical glass of the present invention will be described below. <Refractive index and Abbe number> The refractive index of optical glass (n d ) and Abbe number (ν d ) has been tested in accordance with the method specified in GB / T 7962.1-2010. In some embodiments, the refractive index (n d ) has a lower limit of 1.85, preferably a lower limit of 1.86, and more preferably a lower limit of 1.88; and the refractive index (n d ) is 1.91, preferably 1.90. In some embodiments, the Abbe number (ν d The lower limit of the Abbe number (ν d ) is 38.5, preferably 37.5, and more preferably 37.

[0047] <density> The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010. In some embodiments, the density (ρ) of the optical glass of the present invention is 5.50 g / cm 3 Less than 5.40 g / cm 3 Less than or equal to 5.30 g / cm 3 More preferably, 5.20 g / cm 3 The following is the result.

[0048] <Thermal expansion coefficient> Thermal expansion coefficient of optical glass (α 100 / 300℃) is measured at 100 to 300°C according to the method specified in GB / T7962.16-2010. In some embodiments, the thermal expansion coefficient (α 100 / 300℃ ) is 100 x 10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 90×10 -7 / K or less.

[0049] <Transition temperature> Transition temperature of optical glass (T g ) is tested in accordance with the method specified in GB / T7962.16-2010. In some embodiments, the transition temperature (T g ) is 620°C or less, preferably 610°C or less, and more preferably 600°C or less.

[0050] <Coloring degree> The short-wave transmission spectrum characteristics of the glass of the present invention are coloration (λ 70 and λ5). 70 λ refers to the wavelength at which the glass transmittance reaches 70%. 70 The measurement is performed by using a glass having a thickness of 10±0.1 mm and two mutually parallel flat surfaces that have been optically polished, and measuring the spectral transmittance in the wavelength range from 280 nm to 700 nm, and indicating the wavelength at which the transmittance is 70%. The spectral transmittance or transmittance is the intensity I in The light with intensity I out When light of λ is emitted from a single plane, it is expressed as Iout / Iin, and includes the transmittance of the surface reflection loss at the surface of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, for high refractive index glass, λ 70 The smaller the value, the less coloring there is in the glass itself and the higher the light transmittance.

[0051] In some embodiments, the λ 70is 410 nm or less, preferably λ 70 is 405 nm or less, more preferably λ 70 is 400 nm or less, and more preferably λ 70 is less than 395 nm. In some embodiments, the λ5 of the optical glass of the present invention is 375 nm or less, preferably λ5 is 370 nm or less, more preferably λ5 is 365 nm or less, and even more preferably λ5 is 360 nm or less.

[0052] <Acid resistance stability> Acid resistance stability of optical glass (D A ) (powder method) is tested according to the method specified in GB / T 17129. In some embodiments, the acid resistance stability (D A ) is class 3 or more, preferably class 2 or more, and more preferably class 1.

[0053] <Water resistance stability> Water resistance stability of optical glass (D W ) (powder method) is tested according to the method specified in GB / T 17129. In some embodiments, the water resistance stability (D W ) is class 2 or more, preferably class 1.

[0054] < crystal Upper limit temperature> Glass using the temperature gradient furnace method crystal Glass samples measuring 180 x 10 x 10 mm were prepared, the sides polished, and the temperature was raised to 1300°C in a furnace with a temperature gradient (10°C / cm) and kept at that temperature for 4 hours. After that, the samples were taken out and naturally cooled to room temperature. The glass was then examined under a microscope. crystal Observe the situation and determine the maximum temperature at which crystallization occurs. crystal This is the upper limit temperature. In some embodiments, the optical glass of the present invention crystal The upper limit temperature is 1250°C or lower, preferably 1200°C or lower, more preferably 1180°C or lower, and further preferably 1160°C or lower.

[0055] [Method of manufacturing optical glass] The manufacturing method of the optical glass of the present invention is as follows: The glass of the present invention is manufactured by conventional raw materials, including but not limited to carbonates, nitrates, sulfates, hydroxides, and oxides, and by conventional processes. After blending by a conventional method, the prepared furnace material is put into a melting furnace (such as a platinum crucible or an aluminum oxide crucible) at 1200 to 1400 ° C. and melted. Then, it is clarified, stirred, and homogenized to obtain a homogeneous molten glass without bubbles or unmelted materials, and the molten glass is cast into a mold and annealed. Those skilled in the art can appropriately select the raw materials, manufacturing methods, and process parameters according to the actual needs.

[0056] [Glass preforms and optical elements] A glass preform can be produced from the produced optical glass using press molding means such as polishing, hot press molding, precision press molding, etc. That is, an optical preform can be produced from the optical glass by mechanical processing such as grinding or polishing, or a blank for press molding can be produced from the optical glass, and this blank can be hot press molded and then polished to produce an optical preform, or the blank produced by polishing can be precision press molded to produce an optical preform. The manufacturing method of the optical preform is not limited to the above. As described above, the optical glass of the present invention is useful for various optical elements and optical designs. In particular, it is preferable to form a blank from the optical glass of the present invention, and use this blank to carry out hot press molding, precision press molding, etc. to manufacture optical elements such as lenses and prisms.

[0057] The optical preform and optical element of the present invention are both formed from the optical glass of the present invention. The optical preform of the present invention has the excellent properties of optical glass, and the optical element of the present invention has the excellent properties of optical glass, making it possible to provide optical elements such as various lenses and prisms with high optical value.

[0058] Examples of lenses include various lenses, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens, each of which has a spherical or aspheric lens surface.

[0059] [Optical equipment] Optical elements formed from the optical glass of the present invention can be used to fabricate optical instruments such as photographic devices, imaging devices, display devices, and monitoring devices. EXAMPLES

[0060] <Optical glass examples> In order to further clearly illustrate the technical solutions of the present invention, the following non-limiting examples are provided. In this example, the optical glass manufacturing method described above is used to obtain optical glass having the composition shown in Tables 1 and 2. In addition, the properties of each glass are measured by the test methods described in the present invention, and the results are shown in Tables 1 and 2. [Table 1]

[0061] [Table 2]

[0062] <Glass preform example> The glasses obtained in Examples 1 to 20 of the optical glass are subjected to polishing, hot press molding, precision press molding, or other press molding means to produce various lenses, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, as well as preforms such as prisms.

[0063] <Optical element examples> The preform obtained in the above optical preform example is tempered to fine-tune the refractive index while reducing distortion within the glass so that the optical properties, such as the refractive index, reach the desired values. Each preform is then ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. An anti-reflective coating can also be applied to the surfaces of the obtained optical elements.

[0064] <Optical equipment examples> The optical elements manufactured according to the above optical element embodiments can be used in imaging devices, sensors, microscopes, medical technology, digital projection, communication, optical communication technology / information transmission, optics / illumination in the automotive field, photolithography technology, excimer lasers, wafers, computer chips and integrated circuits and electronic devices containing such circuits and chips, or imaging equipment and devices in the automotive field by forming optical parts or components using one or more optical elements according to optical design.

Claims

1. An optical glass comprising the following components in weight percent: 2 O 3 : 8-20%, La 2 O 3 : 21-40%, Gd 2 O 3 : 6-20%, ZrO 2 :1~10%, ZnO:7~20%, WO 3 : 8-20%, TiO 2 : More than 0 and less than 10%, Y 2 O 3 : More than 0 and less than 10%, Nb 2 O 5 : 0.5-8%, (WO 3 +ZnO) / (La 2 O 3 +TiO 2 +ZrO 2 ) is 0.3 to 1.5, Nb 2 O 5 / Y 2 O 3 is between 0.1 and 2.

5.

2. The optical glass of claim 1 further comprising, in weight percent: SiO 2 : 0 to 9%, and / or Yb 2 O 3 : 0 to 10%, and / or Rn 2 O: 0-10%, and / or RO: 0-10%, and / or Al 2 O 3 : 0 to 5%, and / or Ta 2 O 5 : 0 to 5%, and / or fining agent: 0 to 1%, and the Rn 2 O is for Li 2 O, Na 2 OK 2 O is one or more of MgO, CaO, SrO, BaO, and the fining agent is Sb 2 O 3 , SnO 2 , SnO, CeO 2 is one or more of the following.

3. Required ingredient B 2 O 3 And, La 2 O 3 And, Gd 2 O 3 and ZrO 2 , ZnO, and WO 3 and TiO 2 And, Y 2 O 3 and Nb 2 O 5 Optical glass containing: B 2 O 3 : 8-20%, La 2 O 3 : 21-40%, Gd 2 O 3 : 6-20%, ZrO 2 : 1-10%, ZnO: 7-20%, WO 3 : 8-20%, TiO 2 : 0 to 10%, Y 2 O 3 :0 over 10%, Nb 2 O 5 : 0.5-8%; By weight (WO 3 +ZnO) / (La 2 O 3 +TiO 2 +ZrO 2 ) is 0.3 to 1.5, Nb 2 O 5 / Y 2 O 3 is 0.1 to 2.5, the refractive index n of said optical glass d is 1.85 to 1.91, Abbe number ν d is 32 to 38.5, thermal expansion coefficient α 100 / 300℃ is 100 x 10 -7 / K or less.

4. 4. The optical glass according to claim 3, comprising the following components in weight percent: SiO 2 : 0 to 9%, and / or Yb 2 O 3 : 0 to 10%, and / or Rn 2 O: 0-10%, and / or RO: 0-10%, and / or Al 2 O 3 : 0 to 5%, and / or Ta 2 O 5 : 0-5%, and / or fining agent: 0-1%, Said Rn 2 O is for Li 2 O, Na 2 OK 2 O is one or more of MgO, CaO, SrO, BaO, and the fining agent is Sb 2 O 3 , SnO 2 , SnO, CeO 2 is one or more of the following.

5. Optical glass consisting of the following components by weight: 2 O 3 : 8-20%, La 2 O 3 : 21-40%, Gd 2 O 3 : 6-20%, ZrO 2 :1~10%, ZnO:7~20%, WO 3 : 8-20%, TiO 2 : More than 0 and less than 10%, SiO 2 : 0 to 9%, Y 2 O 3 : 0 to 10% or less, Yb 2 O 3 : 0~10%, Nb 2 O 5 : 0.5~8%, Rn 2 O: 0-10%, RO: 0-10%, Al 2 O 3 : 0 to 5%, Ta 2 O 5 : 0-5%, clarifier: 0-1%, (WO 3 +ZnO) / (La 2 O 3 +TiO 2 +ZrO 2 ) is 0.3 to 1.5, Nb 2 O 5 / Y 2 O 3 is 0.1 to 2.5, Rn 2 O is for Li 2 O, Na 2 OK 2 O, the RO being one or more of MgO, CaO, SrO, BaO, and the fining agent being Sb 2 O 3 , SnO 2 , SnO, CeO 2 is one or more of the following.

6. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent and satisfying one or more of the following eight conditions: 2) Y 2 O 3 / WO 3 is 0.05 to 1.0; 3) Y 2 O 3 / TiO 2 is 0.2-3.5; 4) 5×Nb 2 O 5 / (WO 3 +Gd 2 O 3 ) is 0.05 to 1.5; 5) ZnO / La 2 EITHER 3 は0.2~0.8; 6) Gd 2 EITHER 3 / (The 2 EITHER 3 +Y 2 EITHER 3 )は0.2~0.8; 7) (WO 3 +ZnO) / (The 2 EITHER 3 +TiO 2 +ZrO 2 )は0.5~1.0; 8) 5×Li 2 O / (TiO 2 +SiO 2 ) is 0.05 to 5.0; 9) Nb 2 O 5 / WO 3 is 0.03 to 0.

7.

7. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent: B 2 O 3 : 10-18%, and / or La 2 O 3 : 25-38%, and / or Gd 2 O 3 : 8-18% and / or ZrO 2 : 1 to 8%, and / or ZnO: 8 to 18%, and / or WO 3 : 10-18%, and / or TiO 2 : 0.5 to 7% and / or SiO 2 : 0.5-9%, and / or Y 2 O 3 : More than 0 and 6% or less, and / or Yb 2 O 3 : 0-5% and / or Nb 2 O 5 : 0.5 to 6%, and / or Rn 2 O: 0-5%, and / or RO: 0-5%, and / or Al 2 O 3 : 0 to 2%, and / or Ta 2 O 5 : 0-2%, and / or fining agent: 0-0.5%, Said Rn 2 O is for Li 2 O, Na 2 OK 2 O, the RO being one or more of MgO, CaO, SrO, BaO, and the fining agent being Sb 2 O 3 , SnO 2 , SnO, CeO 2 is one or more of the following.

8. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent and satisfying one or more of the following nine conditions: 1) Nb 2 O 5 / Y 2 O 3 is 0.25-1.5; 2) Y 2 O 3 / WO 3 is 0.1-0.6; 3) Y 2 O 3 / TiO 2 is 0.5-2.0; 4) 5×Nb 2 O 5 / (WO 3 +Gd 2 O 3 ) is 0.1 to 1.0; 5) ZnO / La 2 EITHER 3 は0.3~0.7; 6) Gd 2 EITHER 3 / (The 2 EITHER 3 +Y 2 EITHER 3 )は0.25~0.65; 7) (WO 3 +ZnO) / (The 2 EITHER 3 +TiO 2 +ZrO 2 )は0.6~0.9; 8) 5×Li 2 O / (TiO 2 +SiO 2 ) is 0.1 to 2.0; 9) Nb 2 O 5 / WO 3 is 0.05 to 0.

5.

9. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent: 2 O 3 : 11-17%, and / or La 2 O 3 : 28-35%, and / or Gd 2 O 3 : 9.5-16% and / or ZrO 2 : 2-6%, and / or ZnO: 10-16%, and / or WO 3 : 12-17%, and / or TiO 2 : 1 to 5% and / or SiO 2 : 1-8%, and / or Y 2 O 3 : 1 to 5%, and / or Yb 2 O 3 : 0-2% and / or Nb 2 O 5 : 1 to 5%, and / or Rn 2 O: 0.5-3%, and / or RO: 0-2%, and / or Al 2 O 3 : 0 to 1%, and / or Ta 2 O 5 : 0-1%, and / or fining agent: 0-0.1%, Said Rn 2 O is for Li 2 O, Na 2 OK 2 O, the RO being one or more of MgO, CaO, SrO, BaO, and the fining agent being Sb 2 O 3 , SnO 2 , SnO, CeO 2 is one or more of the following.

10. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent: Gd 2 O 3 : 11-16%, and / or ZnO: 11-16%, and / or SiO 2 : 2-6%.

11. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent and satisfying one or more of the following nine conditions: 1) Nb 2 O 5 / Y 2 O 3 is 0.3-0.8; 2) Y 2 O 3 / WO 3 is 0.1-0.4; 3) Y 2 O 3 / TiO 2 is 0.8-1.3; 4) 5×Nb 2 O 5 / (WO 3 +Gd 2 O 3 ) is 0.15 to 0.5; 5) ZnO / La 2 EITHER 3 は0.35~0.65; 6) Gd 2 EITHER 3 / (The 2 EITHER 3 +Y 2 EITHER 3 )は0.35~0.55; 7) (WO 3 +ZnO) / (The 2 EITHER 3 +TiO 2 +ZrO 2 )は0.7~0.85; 8) 5×Li 2 O / (TiO 2 +SiO 2 ) is 0.2 to 1.0; 9) Nb 2 O 5 / WO 3 is 0.06 to 0.

4.

12. The optical glass according to any one of claims 1 to 5, which comprises the following components in weight percent and which satisfies one or more of the following five conditions: 1) Nb 2 O 5 / Y 2 O 3 is 0.4-0.7; 2) 5×Nb 2 O 5 / (WO 3 +Gd 2 O 3 ) is 0.2-0.4; 3) ZnO / La 2 EITHER 3 は0.4~0.55; 4) 5×Li 2 O / (TiO 2 +SiO 2 ) is 0.3-0.8; 5) Nb 2 O 5 / WO 3 is 0.08 to 0.

3.

13. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent: Li 2 O: 0-6% and / or Na 2 O: 0-5% and / or K 2 O: 0-5%.

14. The optical glass according to any one of claims 1 to 5, comprising the following components in weight percent: Li 2 O: 0.1-3% and / or Na 2 O: 0-2% and / or K 2 O: 0 to 2%.

15. The optical glass according to any one of claims 1 to 5: The ingredients include Ta 2 O 5 and / or GeO 2 does not contain F and / or does not contain Al 2 O 3 does not contain RO and / or does not contain P 2 O 5 Does not contain and / or Bi 2 O 3 The point is that it does not include

16. The optical glass according to any one of claims 1 to 5: The refractive index n of the optical glass d is 1.85 to 1.91, Abbe number ν d is 32 to 38.

5.

17. The optical glass according to any one of claims 1 to 5: The refractive index n of the optical glass d is 1.86 to 1.90, Abbe number ν d is 34 to 37.

18. The optical glass according to any one of claims 1 to 5: Acid resistance stability D of the optical glass A Class 2 or higher and / or water stability D W is Class 2 or higher, and / or density ρ is 5.50 g / cm 3 Below, and / or λ 70 is 410 nm or less, and / or λ 5 is 375 nm or less, and / or thermal expansion coefficient α 100 / 300℃ is 100 x 10 -7 / K or less, and / or the transition temperature T g and / or the upper crystallization temperature is 620°C or less, and / or the upper crystallization temperature is 1250°C or less.

19. The optical glass according to any one of claims 1 to 5: Acid resistance stability D of the optical glass A Class 1 and / or water stability D W is Class 1, and / or density ρ is 5.20 g / cm 3 Below, and / or λ 70 is 400 nm or less, and / or λ 5 is 365 nm or less, and / or thermal expansion coefficient α 100 / 300℃ is 90 x 10 -7 / K or less, and / or the transition temperature T g and / or the upper crystallization temperature is 600° C. or less, and / or the upper crystallization temperature is 1160° C. or less.

20. A glass preform made of the optical glass according to any one of claims 1 to 19.

21. An optical element produced from the optical glass according to any one of claims 1 to 19, or the glass preform according to claim 20.

22. An optical instrument comprising the optical glass according to any one of claims 1 to 19 and / or the optical element according to claim 21.

Citation Information

Patent Citations

  • Optical glass, prefabricated member thereof, optical element and optical instrument

    CN110963700A

  • Optical glass, preform for precision press molding and its manufacturing method, optical element and its manufacturing method

    JP2005247613A

  • Optical glass, preform for precise press-molding and production method therefor, and optical element and production method therefor

    JP2005263570A

  • Optical glass, preform for precision press forming and method of manufacturing the same, optical device and method of manufacturing the same

    JP2007063071A

  • Optical glass, preform for precision press-molding, optical element, and methods for manufacturing the same

    JP2008201661A